Minat Kunjungan Ulang Pasien yang Ditinjau dari Aspek Persepsi dan Kepercayaan pada Klinik Vita Medistra Pematangsiantar - Debi Eka Putri; Onita Sari Sinaga; Hery Pandapotan Silitonga; Susi Susanti Agustina; Acai Sudirman (Inovbiz: Jurnal Inovasi Bisnis, 2020)
The purpose of this study was to determine the effect of perceptions and beliefs on the interests of patient visits at Pematangsiantar Vita Medistra Clinic. Data analysis techniques used by the authors in this study are as follows in the form of quantitative descriptive analysis, Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Test, Coefficient of determination. The object of research at the Vita Medistra Clinic which is located at Jalan Pattimura No. 11 / C Team SBC complex. City 21131, Tomuan Village, Siantar Timur District, Pematangsiantar City, North Sumatra 21139. The results of the study can be concluded as follows: The results of multiple regression repercussions and perceptions have a positive effect on the interest in patient re-visits. Hypothesis test results F-test perception and trust significantly influence the interest in return visits. The results of the t-test perception have a significant effect on interest in the visit, and trust significantly influence the interest of the patient's visit in Pematangsiantar Vita Medistra Clinic. he results of the coefficient of determination of 0.604 means The high or low interest of return visits to the Vita Medistra Clinic by 60.4% can be explained by perception and trust. The company must be a customer perception and trust given by customers about the company to increase interest in repeat visits